Esensi Simbol Sara Douda : Ekspresi Seni Budaya dan Spiritualitas Keimanan Masyarakat Loli Kabupaten Sumba Barat - Sulistyastuti Sutomo; Maya Djawa; Amelia Wila; Fenetson Pairikas; Yakobus Adi Saingo (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The Sara Douda dance is a form of oral tradition cultural art that combines movement elements from original Loli dance accompanied by energetic traditional music, namely gongs and drums, as a powerful medium for expressing the experience of faith, namely gratitude to the Almighty for giving His blessings of life to the Loli community. Sara Douda is full of verbal and non-verbal symbols, rich in meaning, messages and cultural values ​​for the Loli community, used for social interaction and also as an expression of faith in the Most High. The aim of this research is to obtain an overview of the nature, form and meaning of Sara Douda cultural symbols as a form of expression of art, culture and faith of the Loli community in the study of Contextual Theology. This study uses qualitative methods and is analyzed narratively which shows that Sara Douda is a cultural symbol of the Loli people and also a symbol of their faith. Religious symbols allow individuals access to Divine reality and expression. their experience of faith in a cultural context. The verbal and nonverbal symbols in Sara Douda show the Loli Community's faith and belief in God, the Creator of heaven and earth as in the expression Ama wolo Ama rawi. Their offerings of praise and thanksgiving are expressed through poetry in the form of verses and lines as well as beautiful dances from time to time, from generation to generation until now contextual in social life.